The influence of insemination dose on pregnancy per fixed-time artificial insemination in beef cows is affected by semen extender - Crespilho, A. M.; Papa, F. O. [UNESP]; Sá Filho, M. F.; Guasti, P. N. [UNESP]; Dell'Aqua, J. A. [UNESP]; Vasconcelos, J. L.M. [UNESP]; Novaes, J. L.C.; Martins, A. [UNESP] (My University, 2014)
The aim of this study was to compare the efficacy of two extenders (Tris-egg yolk - TRIS and Botu-Bov® - BB, Botupharma, Brazil) for bovine semen cryopreservation with a different number of sperm per straw (6, 12, 25 or 50 × 106 sperm per straw) on post-thaw seminal viability (experiment 1) and pregnancy per artificial insemination (P/AI; experiment 2). In experiment 1, higher values of linearity and straightness associated to low amplitude of lateral head displacement (ALH) were observed in samples cryopreserved with BB extender, when compared to samples cryopreserved with TRIS extender (P < 0.05) regardless of the sperm concentration per straw. The pregnancy rates were 57.63, 60.32, 59.26 and 62.50% respectively for 6, 12, 25 or 50 × 106sperm/straw in BB samples and 45.61, 48.84, 60.34 and 70.59% respectively for the TRIS extender. Increasing the number of sperm had a significant effect on P/AI (P < 0.05) when TRIS extender was used. In conclusion, Botu-Bov® extender promotes better post-thaw sperm movement. The increase in the number of sperm cells per insemination dose improved P/AI rates in Bos indicus lactating beef cows inseminated when using Tris-egg yolk extender.
Keywords: Bovine; Cryopreservation; Fixed time artificial insemination; Semen extender; Sperm number